An inter-institutional working group connects water, energy, food, and ecosystems policymaking in Ethiopia - Balcha, Yodit; Getaneh, Yonas; Abera, Wuletawu (2024)
Since the adoption of the SDGs, recognition has been growing of the need to transition away from traditional, silo-based policy planning towards integrated strategies that balance environmental, social, and economic considerations. Achieving this shift is crucial for fostering inclusive, greener, and more productive economies that can achieve SDG targets. As part of the CGIAR Initiative on NEXUS Gains, the Alliance of Bioversity International and CIAT has catalyzed a significant shift in Ethiopia’s approach to integrated policymaking in the water–energy–food–ecosystems (WEFE) nexus. Starting with the Tana-Beles Sub-basin of the Blue Nile, the initiative has laid the groundwork for true cross-sectoral policy development in Ethiopia. Through a WEFE modeling process in 2023, the initiative established a version of the FABLE Calculator tailored for Ethiopia and also carried out a spatial analysis of the whole Tana-Beles Sub-basin. At the conclusion of this process, the initiative invited 23 sectoral institutions to a group consultation on next steps. That engagement highlighted a strong demand for continued, interactive workshops to refine models, gather diverse insights, and harmonize development targets across sectors.